Performance of hybrid exchange-correlation potential for photocatalytic silver chromate and molybdate: LCAO theory and Compton spectroscopy - Meena, Seema Kumari; Heda, N.L.; Arora, Gunjan; Meena, Lekhraj; Ahuja, B.L. (Physica. B, Condensed matter, 2019)
Linear combination of atomic orbitals (LCAO) method has been employed to compute the Mulliken's population (MP), energy bands, density of states (DOS), band gaps and electron momentum densities (EMDs) of Ag2TMO4 (TM = Cr and Mo). The LCAO prescription has been considered within the framework of density functional theory (DFT) and a newly suggested Hartree-Fock incorporated DFT scheme namely PBESOL0. These approximations for exchange and correlation potentials have been validated by comparing the deduced EMDs with the experimental Compton profiles using 137Cs radio isotope. It is observed that PBESOL0 scheme based EMDs show better agreement with the experimental profiles than other approximations considered in the present work. The energy bands and DOS confirm the semiconducting nature of both the Ag-based oxides. In addition, the relative nature of bonding in both the iso-electronic compounds has also been compared on the basis of equal-valence-electron-density profiles and MP data, which depict that Ag2MoO4 has more ionic character than that of Ag2CrO4. •First-ever Compton profile (CP) measurements of Ag2CrO4 and Ag2MoO4.•Electronic properties and CPs using LCAO scheme and comparison with experiment.•Analysed relative nature of bonding using EVED profiles and Mulliken's population.•Validated use of hybrid HF + DFT (PBESOL0) potential to predict electronic response.